INTEGRATING ARTIFICIAL INTELLIGENCE INTO HUMAN RESOURCE MANAGEMENT: ENHANCING TALENT ACQUISITION, EMPLOYEE ENGAGEMENT, AND PERFORMANCE EVALUATION IN THE DIGITAL ERA (International journal of artificial intelligence, 2024)
In this study we investigate how artificial intelligence (AI) can transform the human resource management (HRM) functions in the banking sector exploring the use of AI within three key areas: Engagement and performance evaluation, as well as talent acquisition. By using AI driven tools in this very competitive, very regulated banking environment, the use of predictive analytics to identify top talent, automated compliance checks and their consequent use of sentiment analysis to track employee satisfaction, have made an impact. These technologies are described in research, how they help solve specific sector challenges, for example automating recruitment of highly specialised roles, or fairness in employee appraisals, given highly prescriptive operating frameworks applicable to banks. Moreover, the evaluated phenomenon illustrates issues of adopting AI from an ethical and operational standpoint, with the potential of these to influence ethics and how the transparency of the AI algorithmic decision making is necessary for market place to continue trusting.Using a mixed method approach consisting of quantitative survey of banking HR professionals and inductive case studies of the leading financial institutions, the study advances a nuanced picture of AI adoption. By critically exploring how AI applications can support workforce adaptation and skill development, it addresses how workforce adaptability and skill development are supported in the scenario of emergent digital banking requirements. What if you think of the story of Machine Learning algorithms predicting the skill gap and suggesting personalized training programs toidual people to be nimble in the crooked road of technological disruptions? This research also describes the context of the banking industry in Uzbekistan, and proposes specific AI enabled HR strategies, applicable within financial sector boundaries and within accounting of industry specific regulatory and cultural factors.The study highlights potential of AI to provide actionable research to help the HRM in banks enhance operational efficiency and increase employee satisfaction and creating a bank’s future ready workforce.